Varieties of Transformational Solutions to Institutional Ethics Logic Conflicts - Nielsen, Richard P. (Journal of business ethics, 2018)
It is well established within the ethics and institutional theory literatures that institutions can have conflicting logics with ethical dimensions and that there are solutions to the conflicts. Within institutional, ethics, and change leadership theory, quantitative, mixture solutions such as distributive solutions have been frequently considered. The ethics, institutional, and change leadership theory literatures have recognized that there are qualitative transformational solutions that are different than quantitative mixture solutions. However and for the most part, with the notable exception of the Thornton et al. (Am J Sociol, 105(3):801–843, 2012) typology of solutions, the institutional, change leadership, and ethics literatures have not considered typologies of transformational solutions. And more specifically with respect to this article, the institutional, change leadership, and ethics literatures have not considered different types of transformational solutions to institutional logic conflicts with ethical dimensions. This article: (1) develops a typology of transformational solutions; (2) applies the typology with historical examples of conflicting institutional ethics logics within factory, cultural, and institutional social change leadership cases; and, (3) considers practical and theoretical implications for institutional ethics change leadership for achieving and/or resisting different types of transformational solutions.